Nitrites on sensory quality of poultry meat cooked hams - AMBROSSIADIS (I. ΑΜΒΡΟΣΙΑΔΗΣ), J.; SOULTOS (Ν. ΣΟΥΛΤΟΣ), N.; VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ), K.; GEORGAKIS (Σ. ΓΕΩΡΓΑΚΗΣ), S. (Journal of the Hellenic Veterinary Medical Society, 2018)
At the present time, the use of nitrites and nitrates are technologically necessary in maintaining flavor, color and texture characteristics associated with and expected of certain stable food items. The effect of nitrite on sensory quality of poultry meat cooked hams was determined. Cooked hams prepared from chicken breast plus 15% brine solution. Four different batters ( A, B, C and D) with 0, 50, 100 and 200 ppm nitrite were made. The samples were cooked in a water bath at 68 °C, then cooled by showering with cold water and stored in 4°C for 8 weeks. The data clearly demonstrated that the nitrite concentration had not influenced in aerobic and lactic acid bacteria counts in the first day after production whilst, there were some unmatchable variations at 8th week of analysis. The residual nitrite contents, the 1st day after production, were 50% of initial amount added. The decrease of nitrite concentration reached 75% at the end of the storage. The addition of 50 and 100 ppm sodium nitrite improved drastically the hue of the surface color whilst, 200 ppm content decreased the a* value (intense of red color) of the samples. Panelists judged Β and C samples better than A and D.